Makna Patriotisme dalam Lirik Lagu Rock Indonesia: Kajian Semiotik Charles Sanders Pierce - Hajriyo, Hajriyo; Pangesti, Nesa Riska (Universitas Negeri Padang, 2024)
This study aims to construct the meaning of patriotism in Indonesian rock song lyrics using Charles Sanders Pierce's semiotic approach. The analyzed songs are